Analisis Variasi Sudut Kampuh V Terhadap Sifat Mekanik Sambungan Las Baja ASTM A36 - Meryanalinda; Muchammad Sochib; Ahmad Habibullah (Wahana Teknik, 2021)
In the book AWS D1.1 the allowable open weld angle is between 60o to 75o, then is there a difference in mechanical strength between the 60o angle and the 75o angle?. This will be studied in this study and aims to compare the effect of variations in the V 60o joint angle with the V 75o joint angle on the mechanical properties of ASTM A36 carbon steel welded joints with with a width of 180 mm and a thickness of 16 mm. This research method using tensile test and vickers test. Tensile test process used to measure the resistance of a material to static forces given slowly. The obtained mechanical properties are known as strength and elasticity of metal. In the tensile test the load is given continuously and slowly increases in size, at the same time observations are made about the elongation experienced by the test object and a stress-strain curve is produced. Hardness testing using the vickers method aims to determine hardness of a material. Based on research that has been carried out, the conclusions are as follows: a) in welding the V 60o seam angle requires a welding electrode of 0.20 kg and in welding a 75o V seam angle requires a welding electrode of 0.27 kg, b) variation of the angle of V 75o has the largest stress value on specimen B2 with a value of 444.25 Mpa, c) specimens with variations in the V 60o joint angle have a higher hardness value than the specimen with a 75o V joint angle variation. Keywords: Analysis, Angle, ASTM A36, Joints, Mechanical, Properties, Steel, Welded, Variation.